Algoritma Pemrograman Numerik Sebagai Solusi Efisien dari Permasalahan Matematika Kompleks - Alya Rahmadani Harahap; Yahfizham Yahfizham (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
Complex mathematics is one branch of the many existing mathematics, where complex mathematics itself discusses and studies complex numbers. Complex numbers are divided into two, namely the real part and the imaginary part. Meanwhile, a programming algorithm is a collection of steps that have a structured nature to solve problems and tasks in the form of programming to achieve certain goals. Programming algorithms can design efficient solutions to various challenges. Utilizing programming algorithms requires logical thinking, to analyze problems in as much detail as possible with in-depth understanding in order to get the desired results. This article uses a literature study method with qualitative research to find out how to solve complex mathematical problems using numerical programming algorithms. This article also aims to explain the close relationship between complex mathematics and numerical programming algorithms as a form of problem solving. In programming algorithms code is needed as a representation of complex numbers, in complex mathematics it also helps to understand how to store and manipulate and form program code.